Preparation Sequence of a 3-Unit Fixed Partial Denture - Sergio Ortegon; Raymond Koeppen; Chanseop Park (Association of American Medical Colleges, 2011)
Abstract This resource is a video that illustrates a straightforward tooth-preparation sequence for a three-unit fixed partial denture. Reduction accuracy and preparation draw are emphasized through the use of reduction guides and paralleling grooves. The demonstration is recorded on a typodont with Ivorine teeth, using carbide and diamond burs. The video depicts the step-by-step preparation process taught to dental students, prosthodontics residents, and preceptors by the Prosthodontics Department at the University of Texas Dental Branch at Houston. This video is an excellent communication tool that places tooth-preparation techniques in the hands of dental students and residents any time they choose. It also maximizes the students' comprehension and learning experience since they have infinite opportunities to review the material prior to and after class. The video could also be used as a continuing clinical aid, which students can rely upon prior to treating their patients in clinic. It is, by far, a superior communication tool when compared to a static PowerPoint presentation, since the students can observe a live demonstration of abutment preparation for a three-unit fixed partial denture.